Politik Uang dalam Pilkada Kota Tual: Perspektif Hukum Positif Indonesia dan Hukum Pidana Islam - Muhammad Iqbal Matdoan; Abubakar Kabakoran; Abdul Muher (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
This research analyzes the practice of money politics in the Tual City Regional Head Election (Pilkada) from the perspectives of Indonesian positive law and Islamic criminal law. Money politics constitutes a violation of democratic principles and the principles of honest and fair elections. Normatively, Indonesian positive law has prohibited money politics through Law Number 7 of 2017 concerning General Elections and Law Number 10 of 2016 concerning the Election of Governors, Regents, and Mayors. However, the implementation of law enforcement in Tual City has not been optimal due to evidentiary constraints, low public participation, and a transactional political culture. From the perspective of Islamic criminal law, money politics is categorized as risywah (bribery) which is forbidden (haram) because it contradicts the principles of justice ('adl), trustworthiness (amanah), and honesty. This research employs an empirical normative legal method with statutory, conceptual, and comparative approaches. Data were obtained through literature review and in-depth interviews with 14 informants from the General Election Commission (KPU), the Election Supervisory Body (Bawaslu), religious leaders, community leaders, academics, and the people of Tual City. The findings indicate that economic factors, low levels of political education, and patron-client culture are the primary causes of the persistent practice of money politics. Addressing money politics requires a comprehensive approach through firm law enforcement, sustained political education, strengthening moral and religious values, and improving community welfare.